2019
DOI: 10.15366/rimcafd2019.73.005
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias Motoras en Atletas Cadetes De Taekwondo Según Nivel Competitivo

Abstract: De la Fuente, A. y Gómez-Landero Rodríguez, L.A. (2019). Diferencias motoras en atletas cadetes de taekwondo según nivel competitivo / Motor Differences in Cadet Taekwondo Athletes According to Competition Level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Flexibility, which is defined as the intrinsic ability of tissues to achieve the maximum range of movement without sports injury [1], is one of the key components of athletic performance together with strength, endurance, speed, and coordination [2][3][4][5]. The range of motion (ROM) in quantitative terms (degrees) represents the indirect measurement of muscle extensibility [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Flexibility, which is defined as the intrinsic ability of tissues to achieve the maximum range of movement without sports injury [1], is one of the key components of athletic performance together with strength, endurance, speed, and coordination [2][3][4][5]. The range of motion (ROM) in quantitative terms (degrees) represents the indirect measurement of muscle extensibility [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…When ROM values have been evaluated in sport, it has been observed a great variation between different sports [9] and even within the same sport, depending on joint and movement [7], sex [9,10], age [11], competitive level [12,13], lateral dominance (dominant and non-dominant) [14], and/or tactical position [15,16]. Likewise, different studies have shown that the restriction in these ROM values could negatively affect sports performance [17][18][19] and increase the injury risk [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dependiendo de las demandas físico-técnicos deportivas, cada deporte manifiesta un diferente grado de exigencia en el ROM de varios o todos los movimientos del perfil de flexibilidad. En este sentido, se han observado valores superiores de ROM en los deportistas con un nivel competitivo superior, lo que contribuye a un mayor rendimiento físico-técnico deportivo (Battista et al, 2007;De la Fuente & Gómez-Landero, 2019;Gannon et al, 1999;Sánchez-Sánchez et al, 2014). Estudios previos, que han evaluado la influencia del ROM sobre el rendimiento de determinados tests físico-técnicos, han observado que los deportistas (voleibol, fútbol) y adultos jóvenes físicamente activos con valores más altos de ROM en la cadera (flexión), rodilla (flexión) y tobillo (dorsiflexión) mostraban un mayor rendimiento en el salto vertical (Faiss et al, 2009;García-Pinillos et al, 2015;Lee et al, 1989;Rey et al, 2016), sprint (García-Pinillos et al, 2015), equilibrio dinámico (Aslan et al, 2018;Basnett et al, 2013;Kang et al, 2015;Overmoyer & Reiser, 2015), agilidad (García-Pinillos et al, 2015;Rey et al, 2016).…”
Section: Introductionunclassified
“…Ante estos hechos, los entrenadores personales, preparadores y readaptadores físicos precisan de valores de referencia del perfil de flexibilidad que determinen los objetivos cuantitativos de entrenamiento de la flexibilidad atendiendo a la especificidad de esta habilidad motora básica como el tipo de deporte (Hogg et al, 2018;Moreno et al, 2004), sexo De la Fuente & Gómez-Landero, 2019;Hogg et al, 2018) y etapa federativa (Cejudo, Robles-Palazón, Ayala, et al, 2019) según el modelo de desarrollo deportivo a largo plazo citado previamente. El perfil de flexibilidad óptimo ha sido determinado previamente con valores iguales o superiores al percentil 80 en cada movimiento de una muestra de jugadores en deportistas (Cejudo et al, 2017;Sainz de Baranda et al, 2015a).…”
Section: Introductionunclassified